If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12*6-(4+2)=0
We simplify the equation to the form, which is simple to understand
-12*6-(4+2)=0
Simplifying:
-72-(4+2)=0
Simplifying terms in parentheses
-72-(+6)=0
Remove unnecessary parentheses
-72-6=0
We move all terms containing to the left and all other terms to the right.
0=0+72+6
We simplify left and right side of the equation.
0=+78
0=78
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 8ax-6x-12a+9=0 | | 16x=1248 | | (-12*6)-4+2= | | 15-2n=n-1 | | 3/4-7/20 | | -7/6=-2n+7/3n | | -12*6-4+2= | | 7/5-3/8k=-2 | | 12(12v+12)-10=2+12v | | 48-6/(3*2)= | | 1/12+x=1/4 | | 48-(6/3)*2= | | (48-6)/3*2= | | 5+-8y=9y+2 | | -3y=-3-x | | 4.5(r-4)=-3(r-1.5) | | .05x+.13(x-3)=.2(x-2) | | 3x-8=6x+1 | | 3h^2+5h/h | | 48-6/3*2=7 | | X^2-2mx+1=0 | | 48-6/3*2= | | 1.2x+6=30 | | 35-5(2x+3)= | | b^2+64=0 | | 36x^2+344x-160=0 | | 2x+11=-13 | | X^2=25/36 | | 2x^2+13a-7=0 | | 10x-3(8-5x)= | | -8c-1=-3 | | 3ay^2+9a=0 |